Insurance of No-fault Responsibility in Medicine - Džidić, Miroslav; Maleta, Nikolina (Medicine, Law & Society, 2018)
Professional liability insurance in medicine based on the no-fault principle is not a novel legal concept, but it has gained popularity in recent years. The reason for this is because the classic professional liability system that exists in most European countries is obsolete. The basic shortcomings of the traditional insurance model are the overwhelming amount of litigation before the courts and the associated costs that are associated with it. At a time when modern medicine emphasizes the importance of patient education and awareness, which includes also informing patients of both their legal rights and obligations in connection with the medical treatment process, it is very difficult to retain the traditional insurance model where the physician’s liability is premised solely on the physician’s fault. Medicine is a humane profession and as such requires the greatest possible protection for health care users as well as for those who perform this extremely important activity for the society. This paper emphasizes the advantages of the no-fault liability insurance model and compares it with other insurance models in the field of medicine. The authors make suggestions for possible reforms to the classic medical professional liability insurance model in Bosnia and Herzegovina. Zavarovanje poklicne odgovornosti v medicini, ki temelji na nekrivdnem načelu, ni nov pravni koncept, a je v zadnjih letih pridobil na priljubljenosti. Razlog za to je, ker je klasični sistem poklicne odgovornosti, ki obstaja v večini evropskih držav, zastarel. Osnovne pomanjkljivosti tradicionalnega zavarovalnega modela so velika količina sodnih sporov pred sodišči in z njimi povezani stroški. V času, ko sodobna medicina poudarja pomen izobraževanja in ozaveščenosti pacientov, kar vključuje tudi obveščanje pacientov o njihovih pravicah in obveznostih v zvezi s postopkom zdravljenja, je zelo težko ohraniti tradicionalni model zavarovanja, kjer je odgovornost zdravnika vezana zgolj na krivdo zdravnika. Medicina je humani poklic in kot taka zahteva največjo možno zaščito za uporabnike zdravstvenega varstva in za tiste, ki opravljajo to izjemno pomembno dejavnost za družbo. Ta članek poudarja prednosti modela zavarovanja nekrivdne odgovornosti in ga primerja z drugimi zavarovalnimi modeli na področju medicine. Avtorja podajata predloge za morebitne reforme modela klasičnega zdravstvenega zavarovanja poklicne odgovornosti v Bosni in Hercegovini.